Some notes on ecophonetics: the problem of sound distinctiveness, sound sustainability, and the sustainability of vowel systems in contact conditions as exemplified by the standard Polish vowel system in contact with the Kashubian vowel system - Puppel, Stanisław (Studia Germanica Posnaniensia, 2018)
In the paper, an assumption is forwarded that if sound systems are brought to a contact setting, inter-entity distinctiveness is usually distorted. In the psycholinguistic sense of the word, it means that in the perception process, a particular sound of a less favoured system may be downgraded or even ridiculed. This generally places a given sound system in a weaker position sustainability-wise. It is assumed that the process may involve the presence and operation of the phenomenon of ethnic nepotism.